The Influence of Customer Experience and Trust on Customer Loyalty PT. Lion Parcel Bengkulu City - Engki Yovanda; Abdul Rahman; Ida Anggriani (Penerbit Jurnal Indonesia, 2022)
The number of people who send goods make delivery services. The distance between the sender and the receiver is getting infinite and the distance. One of the shipping services that are in demand is PT. Lion Parcel. First time in Bengkulu, PT. Lion Parcel is present at the Fatmawati Soekarno airport complex No. 10 RT. 08 Jln. Raya Padang Kemiling of Pekan Sabtu Urban Village, Selebar. PT. Lion Parcel gave his trust to Mr. M. Nopian Rafik because at that time he had a good relationship with Lion Air Group which at that time had a tour and travel business, namely PT. IdamanTour and Travel Based on the results of research and discussions that have been carried out previously, it can be concluded as follows: 1) The test results for the X1 variable (customer experience) show a significance value of 0.000 <0.05. Because the significance value is less than 0.05, X1 (customer experience) has a positive and significant effect on Customer Loyalty (Y). 2) The test results for the X2 (trust) variable show a significance value of 0.000 <0.05. Because the significance value is less than 0.05, X2(trust) has a positive and significant effect on Customer Loyalty (Y). 3) Based on the results of hypothesis testing with the F test, a significance value of 0.000 <0.05 and a significance level below 0.05 indicates that together customer experience (X1) and trust (X2) have a positive and significant effect on customer loyalty(Y). 4) the value of the coefficient of determination of the value of R2 (R Square) is 0.414. This means that customer experience (X1) and trust (X2) affect customer loyalty (Y) by 41.4% while the remaining 58.6% is affected by other variables not examined in this study.